Internalisasi Nilai Luhur Ahlu Sunnah wal Jama’ah Bagi Pengembangan Karakter kebangsaan Di Perguruan Tinggi - Umi Musaropah; Muhamad Mahali; Daluti Delimanugari; Agus Suprianto; Taufik Nugroho (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2020)
This analytical descriptive study intends to see the formation of national characteristics conditioned in supporting learning milliu at PTKI characterized by the Nahdlatul Ulama organization that adheres to the noble values ​​of Ahlu Sunnah wal Jamaah (Aswaja). Mainly, the cultivation of nationalism which is characterized by religion in the tridarma of higher education that can be felt by students as adult students. The research is limited to the process of internalizing characteristic courses that contain local wisdom, or also known as NU-ness, at the Yogyakarta Islamic College (STAIYO) Wonosari. Case studies are conducted qualitatively. After the data from participatory observation, in-depth interviews, and documentation were analyzed, it was concluded that the level of participation of students and all STAIYO academicians was very high. This is because they realize that in the future they will become community leaders who have to protect the religious reasoning as NKRI.